Influencia de la terapia ocupacional en la prevención del deterioro cognitivo en adultos mayores de Cayambe - Aguilar Bosmediano, María José (2017)
Occupational therapy, an intervention strategy that has been positioning itself slowly as one of the therapeutic tools used by many mental health professionals in primary, secondary and tertiary prevention in geriatric patients at a cognitive level, shows that its effectiveness is based on the use of occupation, to improve the quality of life in older adults in a comprehensive way. Hence, older adults in the current context of an active society, have tried to join different activities through the occupational therapy in order to have the opportunity to stay active and lucid to continue to face the challenges of this stage of development. For this reason, this study has as main objective, to prove the influence of Occupational Therapy as a preventive method in the primary cognitive decline in older adults. The methodology used for the scope of this objective shall be comprised of a quantitative approach, with scope of a descriptive nature that allow you to specify what is this influence. In addition, the design employed will be quasi-experimental, the sample that will be used will be older adults between 60 and 80 years of age of a public geriatric center of the city of Cayambe, that is to say that this sample will be probabilistic as it will need to be adjusted to the inclusion and exclusion criteria previously established. This sample will be assigned in two groups, an experimental group and a control group, which will be evaluated before and after the implementation of the occupational therapy. Then, the data analysis to be developed will be one sample and two samples t-tests plus a test of homogeneity of the sample. With this analysis it is possible to determine whether there is a statistically significant difference in order to ascertain whether or not the influence of occupational therapy in the prevention of cognitive decline. In addition to this, this study will contribute in a positive way with knowledge that open to more indepth studies on the effectiveness of the occupational therapy in geriatric populations. And finally, with a proposal of intervention that will surely be very useful for our Ecuadorean context from a psychological approach.